Application of implementation mapping to develop strategies for integrating the National Diabetes Prevention Program into primary care clinics - Perkison, William B.; Rodriguez, Serena A.; Velasco-Huerta, Fernanda; Mathews, Patenne D.; Pulicken, Catherine; Beg, Sidra S.; Heredia, Natalia I.; Fwelo, Pierre; White, Grace E.; Reininger, Belinda M.; McWhorter, John W.; Chenier, Roshanda; et al. (Frontiers in Public Health, 2023)
Background: Diabetes is considered one of the most prevalent and preventable chronic health conditions in the United States. Research has shown that evidence-based prevention measures and lifestyle changes can help lower the risk of developing diabetes. The National Diabetes Prevention Program (National DPP) an evidence-based program recognized by the Centers for Disease Control and Prevention; it is designed to reduce diabetes risk through intensive group counseling in nutrition, physical activity, and behavioral management. Objective: We used Implementation Mapping, a systematic planning framework, to plan for the adoption, implementation, and maintenance of the National DPP in primary care clinics in the Greater Houston area. We followed the framework’s five iterative tasks to develop strategies that helped to increase awareness and adoption of the National DPP and facilitate program implementation. Methods: We conducted a needs assessment survey and interviews with participating clinics. We identified clinic personnel who were responsible for program use, including adopters, implementers, maintainers, and potential facilitators and barriers to program implementation. Evidence- and theory-based methods were selected and operationalized into tailored strategies that were executed in the four participating clinic sites. Implementation outcomes are being measured by several different approaches. Electronic Health Records (EHR) will measure referral rates to the National DPP. Surveys will be used to assess the level of the clinic providers and staff’s acceptability, appropriateness of use, feasibility, and usefulness of the National DPP, and aggregate biometric data will measure the level of the clinic’s disease management of prediabetes and diabetes. Results: Participating clinics were not aware of the National DPP. Steps for planning implementation strategies included the development of performance objectives (implementation actions) and identifying psychosocial and contextual implementation determinants. Implementation strategies included provider-to-provider education, electronic health record optimization, and the development of implementation protocols and materials (e.g., clinic project plan, policies). Conclusions: The National DPP has been shown to help prevent or delay the development of diabetes among at-risk patients. Yet, there remain many challenges to program implementation. The Implementation Mapping framework helped to systematically identify implementation barriers and facilitators and to design strategies to address them.